PERAN PROFITABILITAS, INVESTMENT OPPORTUNITY SET, LIKUIDITAS DAN UKURAN PERUSAHAAN DALAM MEMBERI PERUBAHAN PADA KEBIJAKAN DIVIDEN - Munfarida, Himmatul; Istanti, Sri Layla Wahyu (ANALISIS, 2025)
Business profits distributed as dividends by companys to investors are known as dividend policy. This study focuses on examining how the roles of profitability, investment opportunity groups, liquidity, and company size impact the dividend policy of banking businesses from 2019 to 2023. Banking companies that meet the criteria and are listed on the IDX from 2019 to 2023 are the subjects of this study. The data was collection process was documented using purposive sampling techniques. This study involves eight companies used as samples, with a total of 40 observations. Quantitative methods were implemented in this study. Multiple linier refression analysis was conducted as the analytical tehnique used in this study with the assistence of the SPSS program. This study addresses the implementation objectives where profitability findings show a negative insignificant relationship with dividen policy, while investment opportunity, liquidity and firm size is show a positive but insignificant relationship with dividend policy. The findings from the determination test show that the variables of profitability, investment opportunity set, liquidity, and firm size contribute 1,5% to the divident policy variable in this study model.